Urinary Apolipoprotein A1 and Neutrophil Gelatinase-associated Lipocalin in Children with Idiopathic Nephrotic Syndrome - Suresh Murugesan; Abhijeet Saha; Bobbity Deepthi; Manpreet Kaur; Trayambak Basak; Shantanu Sengupta; Vineeta Batra; Ashish Dutt Upadhyay (Saudi Journal of Kidney Diseases and Transplantation, 2023)
Urinary biomarkers are a promising diagnostic modality whose role was explored in nephrotic syndrome (NS). We estimated urinary apolipoprotein A1 (Apo A1) and neutrophil gelatinase-associated lipocalin (NGAL) in children with first-episode NS (FENS) and controls with a longitudinal follow-up to see the serial changes during remission. The study groups comprised 35 children with FENS and an equal number of age- and sex-matched controls. Patients were followed up at regular intervals, and 32 patients were classified as having steroid-sensitive NS (SSNS) and 3 as having steroid-resistant NS (SRNS). The mean follow-up period was 8.7 ± 4.2 months. Three patients in the SSNS group were labeled as having frequent relapses or steroid-dependent disease during follow-up. Of the three children with SRNS, two had minimal changes in the disease and one had idiopathic membranous nephropathy. The levels of Apo A1:creatinine, NGAL:creatinine, and spot urinary protein:urinary creatinine ratios were significantly higher in children with FENS compared with controls. The levels of the urine biomarkers decreased significantly at subsequent follow-up with remission. The Apo A1 and NGAL levels in SSNS patients were significantly high compared with both the controls and FENS patients. Urinary Apo A1 levels in SRNS patients were lower at initial presentation. This longitudinal study revealed changes in the urinary Apo A1 and NGAL in NS over the course of the disease.